Robustness and efficiency of voting consensus protocols within byzantine infrastructures - Angelo Capossele (Elsevier, 2021)
This paper investigates several voting consensus protocols with low computational complexity in noisy Byzantine infrastructures. Using computer simulations, we show that explicit randomization of the consensus protocol can significantly increase the robustness towards faulty and malicious nodes. We identify the optimal amount of randomness for various Byzantine attack strategies on different kinds of network topologies.